Fifty shades of academic resilience - Santaoja, Minna (Journal of Praxis in Higher Education, 2024)
Resilience is a requirement for a modern-day academic citizen. This essay discusses the sources of academic resilience and its costs through personal reflection. The text positions academic citizenship among intersecting lifeworlds and ends up with a recognition of posthumanist ethic as a source of resilience. The vision for the academic citizen is neither utopian nor dystopian but thrutopian. Academic resilience is persistence to muddle through hardships, drawing power from the anxiety of neoliberal academia in a multicrisis world. The keyboard is our tool for crafting better futures, and the love for writing must be salvaged repeatedly from the paralyzing anxiety that has little in common with academic procrastination memes.